Counterinsurgency Wars and the Anglo-American Alliance : The Special Relationship on the Rocks - Mumford, Andrew, 1983- (Book collections on Project MUSE., 2017)
Andrew Mumford challenges the notion of an actual US-UK "special relationship," the most vaunted, and Mumford says, exaggerated of diplomatic associations in the post-1945 era. This book combines for the first time an analysis of US-UK interaction during major counterinsurgency campaigns since 1945, from Palestine to Iraq and Afghanistan, with a critical examination of the widely perceived diplomatic and military "special relationship." An assessment of each nation's respective private political perceptions and public diplomacy towards the others' conflicts reveals that in actuality there is only a thin layer of "specialness" at work in wars that shaped the postcolonial balance of power, the fight against Communism in the Cold War, and the twenty-first century "War on Terror." This work is especially timely given Britain's changing international relations as a result of Brexit as well as the Chilcot Inquiry about the lead up to the invasion of Iraq in 2003.